(untitled) (Journal of Educational Sciences, 2016)
In the basis of mutual learning is the principle of direct participation, which obliges teachers to make each student participant of the educational process, the current leading search of ways and means of solving the discussed problem. Peer learning allows to develop knowledge, abilities, skills by involving students in active learning-cognitive activity. Micro teaching is a specially organized activity students mimic the real living, pedagogical process which combines both academic andwide elements. Developed Protocol communication activities of the student role of the teacher. The use of mutual learning gives students the qualities of the researcher as creativity, lateral thinking, activity, creativity, ability to establish contact, exchange information, generate the necessary point of view to analyze and evaluate the actions, the ability to clearly and convincingly Express his thoughts.